Spatiotemporal Analysis of Dust Devils in the Preselected Landing Area for Tianwen-3: A Case Study of Chryse Planitia - Yu Yang; Bo Li; Zhaojin Rong; Shaojie Qu; Xuan Cheng (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2025)
Tianwen-3 Mars Sample Return Mission is scheduled for launch in 2028, with a return expected in ∼2030. Dust devils (DDs) play a crucial role in the thermal structure of the Martian atmospheric boundary layer. Additionally, the formation process of dust devil tracks (DDTs) is similar to the process of cleaning dust from solar panels and DDs are more effective than ambient winds in dust removal. A spatiotemporal analysis of DDTs is conducted in Chryse Planitia, a preselected landing area of the Tianwen-3 mission. According to High Resolution Imaging Science Experiment and Context Camera imagery onboard Mars Reconnaissance Orbiter, we identified 3160 newly formed DDTs. The calculated dust lifting rate ranges from 5.12 × 10−2 to 18.65 kg/km2/sol and the DDT formation rates vary between 0.0001 and 0.0176 ddt/km2/sol. Additionally, the solar panel cleaning cycle is from 2.9 to 223.85 sols. Considering the solar panel dust clearing prediction, the spatial probability of dust storms, and the significance in indicating potential biosignatures, the locations corresponding to image pairs 48, 88, and 89 have been selected as the optimal landing sites for the Tianwen-3 mission. These findings provide critical scientific support for the mission’s successful implementation.